2016
DOI: 10.1021/acs.jpca.6b05723
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nitrogen Species as Pollutants: Thermochemical Influences

Abstract: In order to simulate emissions of nitrogen-containing compounds in practical combustion environments, it is necessary to have accurate values for their thermochemical parameters, as well as accurate kinetic values to describe the rates of their formation and decomposition. Significant disparity is observed in the literature for the former, and we therefore present herein high-accuracy ab initio gas-phase thermochemistry for 60 nitrogenous compounds, many of which are important in the formation and consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 41 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…They 99 showed that none of the mechanisms was able to predict the experimental laminar flame speeds on the lean and the fuel rich side at the same time. Testing the impact of the thermodynamic data for NH3, NH2 and NH from Bugler et al 100 we can rule out that the problem is related to thermodynamic properties. However, we are unable to explain where these discrepancies come from.…”
Section: Constant Volumementioning
confidence: 99%
“…They 99 showed that none of the mechanisms was able to predict the experimental laminar flame speeds on the lean and the fuel rich side at the same time. Testing the impact of the thermodynamic data for NH3, NH2 and NH from Bugler et al 100 we can rule out that the problem is related to thermodynamic properties. However, we are unable to explain where these discrepancies come from.…”
Section: Constant Volumementioning
confidence: 99%
“…Rate coefficients for the reactions of n -C 5 hydroperoxyl-alkyl radicals undergoing cyclisation to cyclic ethers and hydroxyl radicals have been updated based on a recent theoretical study by Bugler et al [22] . The pressure dependence of the rate coefficients for these reactions has been calculated via Quantum-Rice-Ramsperger-Kassel/Modified Strong Collision (QRRK/MSC) analyses [31][32][33] .…”
Section: Chemical Kinetic Modelmentioning
confidence: 99%
“…Overall, the disagreement between these rates is acceptable, considering that one of the rates is an estimate. 9 Thermodynamic data from Curran et al 67 was used to compute reverse rates.…”
Section: Calculating Kinetic Parametersmentioning
confidence: 99%